2021
DOI: 10.21203/rs.3.rs-1071201/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smartphone Addiction and its Associated Factors Among Freshmen Medical Students in China: A Cross-Sectional Study

Abstract: Background With the widespread smartphone use worldwide, this has brought about addiction and smartphone addiction recognized as an emerging epidemic. The study aims to investigate the prevalence of smartphone addiction among freshmen medical students and explore its association with personal factors, mental health and professional identity.Methods This cross-sectional study was conducted in October 10th to November 10th, 2020 and included 2182 first-year college students at Wannan Medical College, China.The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Medical students who held religious beliefs exhibited higher scores on the natural acceptance dimension (14,22). Conversely, other studies found that religion did not have a significant impact on death attitudes among medical students (10,11,34).…”
Section: Religionmentioning
confidence: 86%
See 4 more Smart Citations
“…Medical students who held religious beliefs exhibited higher scores on the natural acceptance dimension (14,22). Conversely, other studies found that religion did not have a significant impact on death attitudes among medical students (10,11,34).…”
Section: Religionmentioning
confidence: 86%
“…Sixteen studies have been conducted to assess the influence of religion on medical students' death attitudes (10,11,14,17,19,21,22,25,27,28,34,37,39,41,44). As shown in Table 2, three studies observed a statistically significant distinction between scores of the approach acceptance dimension with and without religion (21,25,28).…”
Section: Religionmentioning
confidence: 99%
See 3 more Smart Citations